Root growth and arbuscular mycorrhizal fungi on woody plants for vegetative stabilization of tropical slopes - I.G. Tejakusuma; E.H. Sittadewi; T. Handayani; T. Hernaningsih; W. Wisyanto; A. Rifai (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Plant growth is improved by arbuscular mycorrhizal fungi, although they have not been researched for slope stability. These fungal inoculations and bamboo interventions may promote root development toward the slip plane. Thstudy looks at how tree roots react to planting in bamboo tubes and the fungal consortium.METHODS: In a screen house, the development of three fast-growing native Indonesian woody plants, Paraserianthes falcataria, Acacia mangium, and Gmelina arborea, was observed. These plants were planted in bamboo tubes filled with soil donated by Jati Radio and Citatah. The tubes were arranged on an inclined plane with a 20° slope. Arbuscular mycorrhizal fungi were introduced in three dosages, with control plots without mycorrhiza and bamboo.FINDINGS: The findings demonstrated that bamboo may drive root development toward the slip plane. On Jati Radio and Citatah soils, the best arbuscular mycorrhizal fungus inoculation results were observed in G. arborea with a treatment dosage of M3 or 30 g. In both sites, neither therapy showed a meaningful change.CONCLUSION: G. arborea has the maximum phosphorus absorption (80%) and biomass weight (660 grams) with M3 dosage in Citatah and 71 percent with 330 g at the same dose in Jati Radio, which is associated with the ideal amount of arbuscular mycorrhizal fungus inoculation. As a result, this species is the best choice for using biotechnological solutions to stabilize slopes in landslide-prone locations. When bamboo is combined with arbuscular mycorrhizal fungi, root development may be directed and accelerated for the purpose of bridging landslide slip planes.